Colour coding-based client segmentation approach: A neglected yet powerful tool to tackle non communicable diseases in high burden and low resource setting countries- A primary care approach - Bhattacharya, Sudip (J Family Med Prim Care, 2020)
Health systems in low- and middle-income countries like India continue to struggle with the overwhelming burden of noncommunicable diseases (NCDs) alongside the coexistence of multiple medical conditions. Such cases are challenging to diagnose and treat, especially in places where electronic health records are not readily available. In such contexts, using colour coding system for recording health conditions may ensure optimal documentation, effective patient-provider communication, adherence to treatment and follow up, quality of health services, and an overall improvement in health systems performance for NCDs. Colour coding is a common tool used in several service industries including public health programmes locally and globally. Despite such promising aspects, colour coding is not widely used for NCDs in health services organizations, which necessitates a translation of evidence from other sectors and the adoption of innovative and evidence-based approaches to promote the use of colour coding for better addressing NCD epidemic.